Teaching Business Leadership Using Non-Business Case Studies: The Mount Everest Example - Roberto, Michael A. (Senate Hall Academic Publishing, 2005)
Non-business case studies, and incidents of catastrophic failure in particular, represent a powerful pedagogical tool for management educators who are designing and delivering leadership courses. This paper explains the lessons that students of business administration can learn from one such case study about the 1996 Mount Everest tragedy. Moreover, it provides management educators with ideas and suggestions for how to use the case to teach important concepts about business leadership, and to draw parallels between the reasons for failure on the slopes of Everest and the causes of failure in various business endeavors.
Keywords: leadership; decision-making; teams; cognitive bias; pedagogy; learning